Positional dependence of transcriptional inhibition by DNA torsional stress in yeast chromosomes - Joshi, Ricky S (Nature Publishing Group, 2010)
How DNA helical tension is constrained along the linear chromosomes of eukaryotic cells is poorly understood. In this study, we induced the accumulation of DNA (+) helical tension in Saccharomyces cerevisiae cells and examined how DNA transcription was affected along yeast chromosomes. The results revealed that, whereas the overwinding of DNA produced a general impairment of transcription initiation, genes situated at <100 kb from the chromosomal ends gradually escaped from the transcription stall. This novel positional effect seemed to be a simple function of the gene distance to the telomere: It occurred evenly in all 32 chromosome extremities and was independent of the atypical structure and transcription activity of subtelomeric chromatin. These results suggest that DNA helical tension dissipates at chromosomal ends and, therefore, provides a functional indication that yeast chromosome extremities are topologically open. The gradual escape from the transcription stall along the chromosomal flanks also indicates that friction restrictions to DNA twist diffusion, rather than tight topological boundaries, might suffice to confine DNA helical tension along eukaryotic chromatin.